Emergence of genetically unrelated NDM-1-producing Acinetobacter pittii strains in Paraguay - Pasteran, Fernando (2014)
The New Delhi metallo-β-lactamase (NDM-1) was initially identified in Escherichia coli and Klebsiella pneumoniae isolates in Sweden, from a patient previously hospitalized in India.1 To date, NDM producers in Latin America have been scarce, and associated with species of Enterobacteriaceae from Guatemala, Mexico, Colombia and Brazil, although in Honduras it was reported in Acinetobacter baumannii.2?6 Here, we report two genetically unrelated NDM-1-producing Acinetobacter pittii isolates identified in Paraguay. Since 1996, the Pan American Health Organization (PAHO) has supported a regional surveillance system, the Antimicrobial Resistance Surveillance Network in Latin America (ReLAVRA), that includes 794 laboratories from 20 Latin American countries, including their respective reference laboratories.7 This network provides reliable, timely and reproducible microbiological data in order to improve patient care. A regional protocol for the detection of carbapenemases has been harmonized and implemented through ReLAVRA. Briefly, metallo-β-lactamase (MBL) production is suspected in isolates that exhibit decreased susceptibility to carbapenems (CLSI criteria) and a positive synergy test result between a disc containing 10 μg of imipenem and a disc containing 750 μg of EDTA plus 1900 μg of sodium thioglycolate.8 During 2012, following the ReLAVRA algorithm, the National Health Laboratory of Paraguay confirmed an MBL phenotype in two Acinetobacter spp. isolates recovered from a single hospital. This phenotype had not previously been observed in Acinetobacter spp. from Paraguay.